Reflections of Positivism in the Political Theory of Evaldas Nekrašas - Stoškus, Mindaugas (Problemos, 2015)
The aim of this article is to discuss the influence of positivism on political theory of Evaldas Nekrašas. The relation between Nekrašasʼ political theory and positivism is ambiguous. On the one hand, the philosopher accepts a positivist distinction between facts and values as well as the anti-metaphysical attitude and the claim that only scientific knowledge based on empirical facts is exact and real. All these allow to state that political theory of Nekrašas was strongly influenced by positivism. On the other hand, the philosopher does not accept a positivist unity between knowledge acquired in natural and social sciences. Nekrašas reveals basic premises of positivism and modern natural sciences, therefore his philosophy crosses the boundaries of positivism.